A study on the factors affecting job satisfaction amongst employees in construction industry workplace (Case Study Saudi Arabia) - Hussein, Ebrahim Mohammed (2018)
This study examines the factors that effect on job satisfaction among employee’s in construction industry in Saudi Arabia. The aims of this study also to identify the relationship between factors of job satisfaction and job/employees performance in construction project. The factors of job satisfaction that examine in this study were salary and compensation, working conditions and workplaces safety, equipment or materials are used, safety condition of the work and attitude toward each other in construction industry, administration and supervision, the expertise of supervisors, the support from supervisors and supervisors‟ communication skills, environment and communication, work and achievement, responsibility, recognition and feedback, the timing of feedback and the chance to be recognised when you done well and lastly the advancement. Employees in construction industry or in any organizations need to be motivated to facilitate their input towards the attainment of their organizational goals. Therefore, to fulfil the gap of previous researchers, the questionnaire of this study asked employees to give their suggestion as well to improve their satisfaction of work. In this research out of 265 surveys were distributed, 117 viable questionnaires were returned. Quantitative method is used in this study and the collected data was analysed by the use of SPSS 20 software with the method of analysed that being used in this research are crosstabs, frequency, percentages, mean and rank. The findings form the study show that Construction Company should pay attention to their employee’s needs and wants to motivate them in order to increase their level of job satisfaction. The concentrates for improvement job satisfaction must focus on the important factors were suggested by responses in this survey.